Case Report: Neuroleptic malignant syndrome in a 15-year-old female following of psychotropic drugs - Fan, Zhao-kun; Yi, Ru-qin; Zhang, Zhi-rong; Shen, Ying-ying (Frontiers in Psychiatry, 2025)
BackgroundNeuroleptic Malignant Syndrome (NMS) is a rare but life-threatening neurological emergency associated with dopamine receptor blockade. It is characterized by hyperthermia, autonomic instability, muscle rigidity, and altered mental status. Early recognition and intervention are crucial to prevent severe complications.Case presentationWe report a case of a 15-year-old female diagnosed with major depressive disorder (MDD), with a body mass index (BMI) of 13.7, who developed severe NMS with rapid-onset rhabdomyolysis and vocal cord dysfunction following an overdose of quetiapine, sertraline, and lorazepam. The clinical presentation posed a diagnostic challenge due to overlapping features with serotonin syndrome. Despite aggressive supportive care, she developed acute kidney injury secondary to rhabdomyolysis, necessitating plasmapheresis and hemoperfusion. Additionally, post-extubation vocal cord dysfunction led to aspiration pneumonia, requiring prolonged airway management.ConclusionThis case highlights the complexity of diagnosing NMS in the context of polypharmacy, the potential for rapid rhabdomyolysis, and the rarity of vocal cord involvement. The successful use of plasmapheresis as an adjunct therapy suggests a possible role in severe NMS with organ dysfunction. Early recognition and individualized management remain key to optimizing outcomes.